Governance Deficit and Nigeria’s Security Quagmire (Journal of Management and Social Sciences, 2020)
AbstractNigeria is currently troubled with a security challenge that poses a threat to the continuing existence of the country as a united corporate entity. Bad governance pioneered by military dictatorship but sustained in the post-military era has been advanced as a major cause of the perennial security crisis. This trend has robbed the nation of peace and security, which are necessary ingredients for sustainable development. This paper employs secondary data and qualitative analysis in the examination of issues involved in using good governance as an antidote for peace and security. The study reveals that good governance remains a viable instrument for achieving peace and security in the country and other developing nations of the world.KeywordsGood governance, peace, security, sustainable development, military dictatorship and democratic governance